2018
DOI: 10.1002/bmc.4323
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of LC–MS/MS and RIA methods for the pharmacokinetics assessment of human insulin in preclinical development

Abstract: Insulin is an effective therapeutic for diabetes, and the level of insulin in vivo is directly related to the health of diabetic patients. Traditionally, the concentrations of insulin in vivo are determined by the radioimmunoassay (RIA) method. In this study, we developed an LC-MS/MS method for the quantification of human insulin in dog plasma and directly compared the RIA and LC-MS/MS methods. Our LC-MS/MS method exhibited superior accuracy, efficiency and cost-effective for the pharmacokinetic (PK) assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…This discrepancy can be attributed to the different methodology used, radioimmunoassays in the older studies ( Narumiya et al, 1982 ) versus quantitative LC–MS/MS in the most recent studies ( Shaik et al, 2014 ) and our studies. LC–MS/MS exhibits superior sensitivity, accuracy, efficiency, and lack of cross-reactivity compared with radioimmunoassays ( Brose et al, 2011 , 2013 ; Dong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy can be attributed to the different methodology used, radioimmunoassays in the older studies ( Narumiya et al, 1982 ) versus quantitative LC–MS/MS in the most recent studies ( Shaik et al, 2014 ) and our studies. LC–MS/MS exhibits superior sensitivity, accuracy, efficiency, and lack of cross-reactivity compared with radioimmunoassays ( Brose et al, 2011 , 2013 ; Dong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is time‐consuming and costly to develop a new radio‐immunoassay method for the quantification of every new insulin analog. In contrast, developing LC–MS/MS methods for insulin quantification is more straightforward, efficient, and therefore has become common in recent years . For example, Chambers et al.…”
Section: Modern Proteomic Technologies For Solving Clinical Biomarkermentioning
confidence: 99%
“…developed an LC–MS/MS method capable of differentiating and simultaneously quantifying human insulin and the therapeutic insulin Glargine. They demonstrated that their LC–MS/MS method was more accurate and efficient for the assessment of human insulin pharmacokinetics than a radio‐immunoassay method …”
Section: Modern Proteomic Technologies For Solving Clinical Biomarkermentioning
confidence: 99%
“…[4][5][6][7][8][9] Other assays using solid phase extraction strongly focus on insulins (without C-peptide) only. [10][11][12] The immune-enriched sample aliquots are of highly purified quality, enabling the injection into nano-scale liquid chromatographs without the risk of blocking due to residual matrix components. The accomplished specificity of these assays were surpassing, but in terms of quantification, several issues may arise: Due to the limited capacity of the antibodies, the linear range of antibody-based assays is restricted and in the case of co-existing anti-insulin antibodies, which were occasionally described in patients with diabetes receiving exogenous insulin therapy, the extraction by means of techniques employing immunoaffinity interaction is potentially affected.…”
Section: Introductionmentioning
confidence: 99%
“…Existing liquid chromatography/mass spectrometry‐based assays mainly use immunoaffinity‐assisted extraction or other sophisticated isolation techniques for the target peptides from the matrix . Other assays using solid phase extraction strongly focus on insulins (without C‐peptide) only . The immune‐enriched sample aliquots are of highly purified quality, enabling the injection into nano‐scale liquid chromatographs without the risk of blocking due to residual matrix components.…”
Section: Introductionmentioning
confidence: 99%